2023
DOI: 10.7759/cureus.40778
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Prostate Cancer Using Tomotherapy With Synchrony Fiducial Tracking

Abstract: Numerous prospective and retrospective studies have demonstrated the efficacy and safety of stereotactic body radiation therapy (SBRT) for prostate cancer. Since SBRT utilizes a very tight margin, management of intrafraction prostate motion is necessary. As a real-time motion tracking and correction system (Synchrony; Accuray, Sunnyvale, CA) has been introduced in the newer platform of tomotherapy (Radixact; Accuray), Radixact can deliver tracking SBRT. In the case report, we present the first clinical experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…One method which will better spare OAR’s and potentially reduce treatment related side effects is the reduction of PTV margins ( 19 ). Reducing PTV margins poses challenges as the prostate exhibits both inter and intra-fraction motion caused by bladder and rectal filling, bowel movement, and skeletal muscular motion ( 20 22 ). Therefore, caution should be employed when implementing margin reductions because advanced imaging technologies and strategies may be required to prevent underdosage of the target ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method which will better spare OAR’s and potentially reduce treatment related side effects is the reduction of PTV margins ( 19 ). Reducing PTV margins poses challenges as the prostate exhibits both inter and intra-fraction motion caused by bladder and rectal filling, bowel movement, and skeletal muscular motion ( 20 22 ). Therefore, caution should be employed when implementing margin reductions because advanced imaging technologies and strategies may be required to prevent underdosage of the target ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate PTV margins ranging from 2 mm to greater than 10 mm have been reported in the literature and this variation often coincides with the type of pretreatment imaging used and whether intra-fraction adaptions are applied (25). Most commonly, PTV margins fall within the range of 4 to 6 mm (22,(26)(27)(28). Keizer et al found that PTV margin reduction below 4 mm would require intra-fraction monitoring and correction (29).…”
Section: Introductionmentioning
confidence: 99%